MOTIVASI KOREA SELATAN MEMPROMOSIKAN BUDAYANYA MELALUI “TEKO NANG JAWA” DI INDONESIA PADA TAHUN 2019 - Maharani Octa Peddyaratri; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The focus of this research is to analyze the motivation of South Korea to promote its culture through the Teko Nang Jawa project in Indonesia. The spread of the Korean Wave in Indonesia encouraged South Korea to promote its culture in Indonesia, particularly in Java. In a new and unique way, the Embassy of the Republic of Korea conducted a bus tour around Java to promote its culture, especially to small towns in Java. Apart from promoting Korean culture, the “Teko Nang Jawa” event also held cultural exchanges in each destination city.This research uses a qualitative explanative method with a level of analysis of the nation-state. The theory used in this research is the theory of diplomacy in the perspective of pluralism. To analyze this research, the authors collected documents from books, journals, websites, dictionaries, as well as various information from the Embassy of the Republic of Korea to Indonesia.Based on the analysis conducted, it is concluded that this study shows that the